Pengaruh Green Marketing Dan Brand Image Terhadap Minat Beli Konsumen - Purnomo, Nanto; Azizah, Luluk Nur (Politeknik Negeri Ambon, 2025)
The purpose of green marketing is not solely to make a profit, but rather the company aims to raise awareness of environmental issues. AQUA's green marketing is carried out through the AQUA campaign, focusing on health, specifically